PENGARUH RASIO KEUANGAN DALAM OPTIMALISASI HARGA SAHAM PERBANKAN - Juwari Juwari; Dwi Susilowati; Muhammad Frisna Firmansyah (Program Studi Manajemen Fakultas Ekonomi Universitas Balikpapan, 2024)
The purpose of this research is to determine the effect of Capital Adequacy Ratio, Net Profit Margin, Return On Assets, Operational Costs, Operational Income, and Non-Performing Loans on Stock Prices. The data used are existing sources, both internal and external company data which can be accessed via the internet and information publications. The data used are the financial reports of state-owned banking companies for the period 2013 - 2022. The method used in this research is multiple linear regression analysis. The results of the analysis show that the Return On Assets and Operational Costs Operational Income variables have a significant negative effect on stock prices. The Capital Adequacy Ratio and Net Profit Margin variables have an insignificant negative effect on stock